2013
DOI: 10.1016/j.jhydrol.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Source and magnitude of error in an inexpensive image-based water level measurement system

Abstract: Recent technological advances have opened the possibility to use webcams and images as part of the environmental monitoring arsenal. The potential sources and magnitude of uncertainties inherent to an image-based water level measurement system are evaluated in an experimental design in the laboratory. Sources of error investigated include image resolution, lighting effects, perspective, lens distortion and water meniscus. Image resolution and meniscus were found to weigh the most in the overall uncertainty of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 13 publications
1
48
0
4
Order By: Relevance
“…Moreover, unmanned aerial vehicles can improve crowdsourced data collection, supporting citizen observatories, lowering data uncertainty, and filling in the gap due to the irregular distribution of engaged volunteers. In agreement with the analysis performed by Gilmore et al [52], the major sources of uncertainty are found to be the perspective and the pixelization, while the scale of the experiment allowed us to get rid of the effect of meniscuses formed by water at the contact with the background. It is worth underlining the fact that the water surface waviness can substantially affect the water level estimates, as waves ripple the water, causing a blurry water level edge.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, unmanned aerial vehicles can improve crowdsourced data collection, supporting citizen observatories, lowering data uncertainty, and filling in the gap due to the irregular distribution of engaged volunteers. In agreement with the analysis performed by Gilmore et al [52], the major sources of uncertainty are found to be the perspective and the pixelization, while the scale of the experiment allowed us to get rid of the effect of meniscuses formed by water at the contact with the background. It is worth underlining the fact that the water surface waviness can substantially affect the water level estimates, as waves ripple the water, causing a blurry water level edge.…”
Section: Discussionsupporting
confidence: 89%
“…The combination of the waves and of both angle and intensity of the incoming light source (e.g., sun, clouds) creates the sharp change in pixel gray scale in an image. Gilmore [52] investigated different sources of uncertainty affecting water level estimates from images. In addition to the uncertainties associated to the local environment as the change in lighting, other sources of uncertainty are associated with the image quality, such as image focus, image resolution, perspective, and lens distortion.…”
Section: Resultsmentioning
confidence: 99%
“…For example, low-cost water quality sensors have been developed and tested for parameters such as pH and conductivity, temperature, toxicity, and turbidity (Banna et al, 2014;Chapin, Todd, & Zeigler, 2014;Murphy et al, 2015;Tuna, Arkoc, & Gulez, 2013;Yagur-Kroll et al, 2015), although few sensors have actually been deployed in the field. Offthe-shelf cameras have also been applied successfully to record water level (Gilmore, Birgand, & Chapman, 2013) and discharge (Bradley, Kruger, Meselhe, & Muste, 2002;Tsubaki, Fujita, & Tsutsumi, 2011), plant phenology (Crimmins & Crimmins, 2008;Nijland et al, 2014), and cloud cover (Scholl, 2015). To compile data, wireless sensor networks can also be used to provide connected and sometimes real-time data on a range of environmental parameters within an area (Kido et al, 2008;Zia, Harris, Merrett, Rivers, & Coles, 2013).…”
Section: New Sensors and Data Loggersmentioning
confidence: 99%
“…Bradley et al, 2002;Muste et al, 2008;Tsubaki et al, 2015), stage (e.g. Shin et al, 2007;Royem et al, 2012;Gilmore et al, 2013;Schoener, 2017) or discharge (Lüthi et al, 2014) found its way into hydrological applications. Streamflow measurements using particle image velocimetry (PIV) require video imagery and have been used in combination with artificial and natural tracers (Bradley et al, 2002;Creutin et al, 2003;Muste et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of measured heights from the camera system with stage heights from the United States Geological Survey (USGS) showed a good agreement with a relative difference of 16 %. Gilmore et al (2013) identified image resolution, lighting effects, perspective, lens distortion and the water meniscus as sources of error. They found image resolution and the meniscus contributing most to errors in detected water level, while the influence of lens distortion largely depends on the consideration of the distortion in the software.…”
Section: Introductionmentioning
confidence: 99%